As they journeyed from the east: the Nahotei of the fourth century and the construction of the Rabbinic diaspora - Schwartz, Marcus Mordecai (Hebrew Union College annual, 2016)
This study assesses the activity of the Nahotei, a group of migrating talmudic rabbis. Responsibility for the importation of the lion's share of Palestinian rabbinic texts to the Babylonian Talmud has traditionally been assigned to this group. This study accepts the assumption that they did indeed import some small number of Palestinian rabbinic materials to Babylonia in the fourth century. However, beating a new path, it also claims that, at least as depicted in b. Seder Mo'ed, they did little more than clarify, modify or reassign the authorship of traditions already known in Babylonia prior to their reports.